2020
DOI: 10.3390/cells9091967
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Role of Sphingolipid Metabolism in Melanoma

Abstract: Cutaneous melanoma is a deadly skin cancer whose aggressiveness is directly linked to its metastatic potency. Despite remarkable breakthroughs in term of treatments with the emergence of targeted therapy and immunotherapy, the prognosis for metastatic patients remains uncertain mainly because of resistances. Better understanding the mechanisms responsible for melanoma progression is therefore essential to uncover new therapeutic targets. Interestingly, the sphingolipid metabolism is dysregulated in melanoma an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 204 publications
0
20
0
Order By: Relevance
“…In melanoma cells, knockdown of SphK1 inhibited the secretion of immunosuppressive cytokines (ex. TGF-β), which sensitized the melanoma cells to anti-PD-1 and anti-CTLA-4 immunotherapies in mice [180][181][182]. S1P secretion from lung cancer cells was also found to impair CD8 positive T cell responses, facilitating metastasis [180].…”
Section: Immunotherapy and Sphingolipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…In melanoma cells, knockdown of SphK1 inhibited the secretion of immunosuppressive cytokines (ex. TGF-β), which sensitized the melanoma cells to anti-PD-1 and anti-CTLA-4 immunotherapies in mice [180][181][182]. S1P secretion from lung cancer cells was also found to impair CD8 positive T cell responses, facilitating metastasis [180].…”
Section: Immunotherapy and Sphingolipidsmentioning
confidence: 99%
“…TGF-β), which sensitized the melanoma cells to anti-PD-1 and anti-CTLA-4 immunotherapies in mice [180][181][182]. S1P secretion from lung cancer cells was also found to impair CD8 positive T cell responses, facilitating metastasis [180]. Patients with bladder cancer were found to have higher levels of S1PR1 and immunosuppressive cytokine secretion (TGF-β, IL-10), along with more circulating and tumor-infiltrating regulatory T cells, which is associated with poor patient outcomes [183].…”
Section: Immunotherapy and Sphingolipidsmentioning
confidence: 99%
“…Cer have been reported to be involved in differentiation, proliferation, growth arrest, and apoptosis [ 67 ]. Several studies have showed that melanoma cells are able to rearrange sphingolipid metabolism by preventing intracellular Cer accumulation by induction of Cer-degrading enzymes and downregulation of Cer-promoting enzymes [ 68 ]. Thus, increasing the intracellular levels of Cer was shown to reduce cancer cell proliferation [ 69 , 70 , 71 , 72 , 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have suggested that the SphK1/S1P axis could play a role in the promotion of several types of tumors, based on the overexpression of SphK1 in tumor cell lines and in patient samples, and sometimes, on the measured increased S1P levels in tumors and/or in patient blood. These studies have recently been reviewed for breast [ 46 ], ovarian, [ 47 ], and gastrointestinal cancers [ 48 ], hepatocellular carcinoma [ 49 ], melanoma [ 50 ] and glioblastoma [ 51 ]. High S1P in breast tumor tissue is significantly associated with lymphnode metastasis [ 52 ].…”
Section: Sphingolipids In Cancermentioning
confidence: 99%